EPISTEMOLOGI KALAM ASY’ARIYAH DAN AL-MATURIDIYAH - Adnin Adnin; Muhammad Zein (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
The emergence of various groups of schools of thought in Islam has given its own color in the Islamic religion. These thoughts arose after the death of the Prophet. There are several factors that cause the emergence of various groups with all of their thoughts. Among them are political factors as there has been a conflict between the Ali group with Muawiyah followers, so that it raises a new group, the khawarij group. Then came the other groups as a reaction from group one to another group. These groups have different thoughts from one another. Some are still in the corridor of the Qur'an and Sunnah, but there are also those who deviate from the two sources of Islamic teachings. There are those who hold the revelation, and some who put excessive reason so that it comes out of revelation. And there are also those who call themselves Ahlussunnah wal Jama'ah. As a reaction from a misguided firqah, at the end of the 3rd century H came a group known as Ahlussunnah wal Jamaah led by two great ulemas in Usuluddin, Sheikh Abu Hassan Ali Al Asy'ari who was the founder of the Ash'ariyah sect and Sheikh Abu Abu Mansur Al Maturidi as the founder of the Maturidiyah school. This Ash'ariah and Maturidiyah school is used in this discussion.Keywords: Epistemology, Asy'ariyah, Al-maturidiyah.